Thermal insulation capability of PEG-containing polyurethane foams - Önder, Emel; SARIER, NİHAL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
Polyethylene glycol (PEG) compounds and mixtures have many properties that make them suitable for thermal applications in buildings, such as having high heat of fusion, phase change repeatability, chemical stability, non-corrosive behavior, and low-cost. In this study, we developed a number of PU rigid foams incorporated with three types of PEGs, as new insulation materials provided with an enhanced thermal capacity, and sought their suitability for various applications Such as layer of floor and ceiling coverings in constructions. insulations in controlled temperature transportation packaging, inner coverings of automobile seats, etc. In order to investigate the thermal properties of PEG-containing PU foams, differential scanning calorimeter (DSC) tests were conducted first. Then, a two-layer concrete-PU foam system was designed in the laboratory conditions to examine the insulation performances via using a computer-aided thermal measurement setup which was sensitive to the simulated environmental temperature changes. The PU-PEG composites produced here can be helpful for the design of thermal insulators. PUI, including 44% PEG 600, exhibited fairly efficient thermal regulation under moderate ambient temperature conditions, whereas PUII (49% PEG 1000) is suitable for temperature control in both mild and hot surroundings. PUIII, containing 53% PEG 1500, showed suitable heat storage and thermal stability characteristics. PUIV, containing 38% PEG 600/PEG 1000/PEG 1500, also confirmed good thermal and durability characteristics. The blend of three PEGs is suitable for preventing discontinuous thermal regulation when the external temperature increases or decreases. PU foams containing PEGs can be assumed to be leak-resistant, which is promising for their industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: polyethylene glycol; PCM; thermal; DSC; polyurethane foam; phase-change materials; storage; wallboard; polietilen glikol; termal; poliüretan köpüğü; faz değiştiren maddeler; depolama; duvar kaplaması